An IDH-independent mechanism of DNA hypermethylation upon VHL inactivation in cancer. Issue 8 (3rd August 2022) - Artemov, Artem V.; Zhenilo, Svetlana; Kaplun, Daria; Starshin, Alexey; Sokolov, Alexey; Mazur, Alexander M.; Szpotan, Justyna; Gawronski, Maciej; Modrzejewska, Martyna; Gackowski, Daniel; Prokhortchouk, Egor B.
ABSTRACT: Hypermethylation of tumour suppressors and other aberrations of DNA methylation in tumours play a significant role in cancer progression. DNA methylation can be affected by various environmental conditions, including hypoxia. The response to hypoxia is mainly achieved through activation of the transcriptional program associated with HIF1A transcription factor. Inactivation of Von Hippel-Lindau Tumour Suppressor gene ( VHL ) by genetic or epigenetic events, which also induces aberrant activation of HIF1A, is the most common driver event for renal cancer. With whole-genome bisulphite sequencing and LC-MS, we demonstrated that VHL inactivation induced global genome hypermethylation in human kidney cancer cells under normoxic conditions. This effect was reverted by exogenous expression of wild-type VHL . We showed that global genome hypermethylation in VHL mutants can be explained by transcriptional changes in MDH and L2HGDH genes that cause the accumulation of 2-hydroxyglutarate – a metabolite that inhibits DNA demethylation by TET enzymes. Unlike the known cases of DNA hypermethylation in cancer, 2-hydroxyglutarate was accumulated in the cells with the wild-type isocitrate dehydrogenases.